Do Contextual and Demographic Factors Help Malaysian Nurses Prepare in Dealing with the COVID-19 Pandemic? - Chua, Bee Seok; Getrude Cosmas; Norkiah Arsat; Walton Wider (MDPI, 2022)
As of 11 October 2020, Sabah comprised a quarter of all COVID19 cases reported in Malaysia since the start of the pandemic last January 2020. In this pandemic, nurses serve in vital roles to mitigate the effects of COVID-19. This study aims to explore the nurses’ preparedness in managing the COVID-19 outbreak situation in Sabah, Malaysia, examining the contextual (e.g., participated in an actual major disaster event) and demographic factors (e.g., age and working experience that may influence nurses’ preparedness for managing the COVID-19 pandemic). A total of 317 nurses in Sabah, Malaysia were involved in this study. The Emergency Preparedness Information Questionnaire (EPIQ) contained 41 items and was used to assess civilian nurses’ perceived familiarity with 9 competency dimensions of preparedness. The mean scores of nurses’ preparedness indicated a moderate level of nurses’ preparedness in managing the COVID-19 pandemic (mean ranging from 2.89 to 3.79). The results indicated that there was a significant difference between the nurses who actively participate in an actual major disaster event and who were not active in a total of preparedness and all dimensions (t = 2.79, df = 285, p = 0.006) (except in familiarity with decontamination and familiarity with special populations), across working experience (F(2,291) = 5.09, p = 0.007) (except familiarity with Incident Command System and role), and age among nurses ((F(3,290) = 2.68, p = 0.047)) (total of preparedness, familiarity with ethical issues in triage, epidemiology, and surveillance, and psychological issues). Overall, this study has made a significant theoretical contribution, as well as in clinical implications in the field of nursing practice, by addressing the impact of contextual and demographic factors on nurses’ preparedness in managing the COVID-19 outbreak situation. This study will help nurses to understand the skills, abilities, knowledge, and actions needed to respond, mitigate, and prepare for emergencies during pandemics and disasters.